Difficulties of cultural diversity: an exploratory study into forensic psychiatric reporting on serious juvenile offenders in the Netherlands - Komen, Mieke (Crime, law and social change, 2006)
This paper discusses psychiatrists' assessments of the personalities of ethnic minority and ethnically Dutch juvenile offenders. Psychiatric reports and recommendations help courts determine the type and duration of sanctions. Psychiatrists are involved in almost all cases of serious juvenile crime, because under Dutch law, determining criminal responsibility is a matter for psychiatrists. The courts usually follow the recommendations of forensic psychiatrists when giving judgment and sentencing juvenile offenders.